The Performance of Coconut Husk and Shell for the Removal of Methyl Red from Aqueous Solution: Adsorption Equilibrium and Kinetic Study - Edriyana, Abd Aziz; Abdul Syukor, Abd Razak; Suryati, Sulaiman; Hasmanie, Abdul Halim; Islam, Mir Sujaul; N. A., Zainodin; W. A., Wan Omar (Medwell Journals, 2016)
Abstract: Removal of methyl red from aqueous solution onto coconut husks and coconut shell, a low cost agricultural waste material in a batch process was investigated. Adsorption and removal was studied as a function of amount of adsorbent (0.02-0.08 g), pH (2.0-12.0) and initial concentration (200-800 mg L–1). Adsorption data were modeled using Langmuir, Freundlich and Tempkin adsorption isotherm models. Equilibrium data of the biosorption process fitted very well into Langmuir isotherm model. The maximum adsorption capacity was approximately 71 mg g–1 for both coconut husks and coconut shell at an optimum pH 12. Adsorption kinetic was verified by pseudo-first order and pseudo-second order kinetic models. The results indicated that the dye uptake process followed the pseudo-second order which suggest that adsorption of the dye was through a chemical sorption. From the removal experiments, the results indicated that coconut husks and coconut shell could not effectively be employed as a low-cost adsorbent for the removal of basic dyes (methyl red) from aqueous solution as its removal is concentration dependent.